The relationship between audit committee, political influence and financial reporting quality: Malaysian evidence / Aziatul Waznah Ghazalia and Nur Aima Shafie - Ghazalia, Aziatul Waznah; Shafie, Nur Aima (Accounting Research Institute (ARI), UiTM Shah Alam, 2019)
This paper examines the relationship between audit committee, political influence and financial reporting quality of Malaysian listed companies. This study consists of pool data of 3,215 firm-year observations listed on the Main Board of Bursa Malaysia from year 2010 to 2014. The study uses logistic regression to test the association between audit committee, political influence and financial reporting quality. The results are also robust with the inclusion of Firth logit analysis. The current findings indicate that audit committee's independence and the frequency of audit committee meetings are effective in controlling for both real earnings management and accounting misstatements. Nonetheless, in terms of audit committee size and audit committee' audit expertise, the relationships are still insignificant. It is important to note that there is some improvement after the corporate governance reforms in 2010 since studies prior to the reforms found audit committee's variables are ineffective towards a higher quality of financial reporting. Meanwhile, political influence is still relevant in a Malaysian business environment with regard to financial reporting quality, however, the aggressiveness of the influence may have been diluted by the improvement of recent corporate governance reform.